ANALISIS PENGARUH LEMBAGA PEMBIAYAAN DALAM MENINGKATKAN UMKM DI INDONESIA - Dian Ariani (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
ABSTRACT  Micro, Small and Medium Enterprises or better known as UMKM have a very important role in increasing the country's growth. These UMKM were able to survive in 1998 compared to large companies in Indonesia. The purpose of this study is to analyze to encourage the development of UMKM in Indonesia and to provide solutions in increasing UMKM. The research method used is a combination of quantitative research with qualitative research (Mixed Methods). The results of this study are UMKM that are looking for very fast financing, which can be used from a variety of jobs, personal and personal and lifestyle. Yes, there are also UMKM that do not innovate or even decline. The decline in UMKM business was caused by two things related to economic conditions and unfavorable conditions. Keywords: UMKM, Mix Methods and Financing Institutions